A Cytogenomic Analysis Reveals a New Fusarium fujikuroi Species Associated with Lemongrass (Cymbopogon citratus) - Tomás Cavaco; Catarina Gomes-Domingues; Filipe Gonçalves (Biology and Life Sciences Forum, 2023)
This study presents the first report of a Fusarium wilt in Cymbopogon citratus in Portugal. Fusarium is one of the most prominent genera of plant pathogens due to its wide range of hosts and mycotoxin production. The Fusarium fujikuroi species complex (FFSC) encompasses several threatening known plant pathogens. Cymbopogon citratus is a broadly distributed aromatic and medicinal plant rich in bioactive volatiles, which are relevant to several industries. The primary goal of this study was to identify and characterize the Fusarium fujikuroi species putatively responsible for the observed wilt. This report displays symptomatologic, cultural, morphologic, genetic, and cytogenomic characteristics associated with this fungus and disease. The cultural features included flat, white-colored colonies with filiform margins. Additionally, these colonies displayed abundant cottony aerial mycelia at the upper surface and orange-violet color at the lower surface. On Carnation Leaf-Piece Agar, septate fusoid macroconidia were present, displaying a flattened tapering toward the basal part and a number of septa ranging from one to four. The comparison between the amplified and aligned ITS sequences revealed 100% similarity between the isolate and the FFSC. Finally, a flow cytometry assay revealed an estimated genome size of 29.9 Mbp. This finding contrasts with other known pathogens from the Fusarium fujikuroi species complex. Ultimately, novel pathogens might be uncovered by exploring the mycobiome of diseased Cymbopogon citratus plants.